Digitalisation and the Economic Productivity Paradox: Empirical Evidence from Developing Countries in Asia - Irfan Mubarok, Fawaz; Ahmad Zainunnuri, Fakhri (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2026)
This study aims to analyse the impact of digitalisation on economic productivity in developing Asian countries within the context of the productivity paradox. The phenomenon of a global slowdown in productivity amidst the rapid development of artificial intelligence (AI), the internet, and digital technology indicates a mismatch between technological progress and increases in economic productivity. The study employs a quantitative approach using panel data regression on 10 developing Asian countries over the period 2005–2024. The research variables consist of GDP as the dependent variable, and internet users (INT), mobile cellular subscriptions (CELL), trade openness (TRADE), gross capital formation (GROSS), and inflation (INF) as independent variables. The research data was obtained from the World Bank via the World Development Indicators (WDI) and analysed using the Random Effects Model (REM). The results indicate that internet users have a positive and significant effect on GDP, whilst inflation has a negative and significant effect on GDP. Meanwhile, mobile cellular subscriptions, trade openness, and gross capital formation do not show a significant effect on GDP. Collectively, all independent variables have a significant effect on GDP, with an Adjusted R-Squared value of 76.47%. This study concludes that digitalisation has not yet been able to optimally boost economic productivity in developing countries in Asia. This situation points to a productivity paradox resulting from disparities in digital infrastructure, low effectiveness in the use of technology, and the fact that digital activities remain predominantly consumptive rather than productive. Humans have succeeded in accelerating cross-border digital connectivity, but have not yet fully succeeded in ensuring that such connectivity actually boosts economic productivity.